Surfactant-Assisted Pressurized Liquid Extraction at Room Temperature for Radix glycyrrhizae by a New Class of Surfactants - Heng, Ming Yuan (J Chromatogr Sci, 2016)
A laboratory-assembled surfactant-assisted pressurized liquid extraction system at room temperature was used for the extraction of glycyrrhizin (GLY) in Radix glycyrrhizae. Environmentally friendly saccharide fatty acid ester such as glucose oleic acid ester is proposed to replace chemical-based surfactants. As the chemical properties of the surfactant obtained were unknown initially, lipase-catalyzed synthesis and liquid chromatography with tandem mass spectrometry were used to ascertain the identity. Surfactant-assisted pressurized liquid extraction (PLE) was carried out dynamically and the extraction efficiencies of the proposed method using different concentration of glucose oleic acid ester were compared with sonication using an organic solvent (ethanol/water, 70:30). The extraction efficiencies of GLY in Radix glycyrrhizae using surfactant-assisted PLE was observed to be higher compared with sonication. The method precision was found to vary from 1.3 to 5.1% (relative standard deviation, RSD, n= 6) on different days. The new method demonstrated the possibility for the extraction to be carried out at room temperature for the production of botanical extracts.